2015
DOI: 10.1016/j.pedneo.2014.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Malformations in the Newborn Population: A Population Study and Analysis of the Effect of Sex and Prematurity

Abstract: We reported up-to-date national estimates of the prevalence of CM, which is important for monitoring trends, determining service planning, and assessing disease burden because of congenital malformations in the United States of America. We also showed a strong association between CM and prematurity. Further study of this association is needed to provide insight into the etiology of these relatively common public health problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
42
1
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 20 publications
6
42
1
8
Order By: Relevance
“…Although a direct comparison was difficult, rates of pregnancy outcomes observed in this trial were found to be close to the reported rates available in the literature. [31][32][33][34][35] These observations are in line with results from pooled analyses and post-marketing studies conducted so far to assess pregnancy outcomes after exposure to AS04-HPV-16/18 vaccine. [36][37][38][39] The study has some limitations.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Although a direct comparison was difficult, rates of pregnancy outcomes observed in this trial were found to be close to the reported rates available in the literature. [31][32][33][34][35] These observations are in line with results from pooled analyses and post-marketing studies conducted so far to assess pregnancy outcomes after exposure to AS04-HPV-16/18 vaccine. [36][37][38][39] The study has some limitations.…”
Section: Discussionsupporting
confidence: 77%
“…Among them, 138 (92%) were seronegative for anti-HPV-31 antibodies and 141 (94%) were seronegative for anti-HPV-45 antibodies at the baseline. All of those who were seronegative for the type analyzed at baseline had seroconverted for HPV- 31 significantly different as the 95% CIs were largely overlapping for both anti-HPV-31 and -45.…”
Section: Serum Antibody Response Against Hpv-31 and Hpv-45mentioning
confidence: 98%
“…Congenital anomalies are among the major causes of infant death worldwide (Brazilian Ministry of Health, MoH) (Egbe et al , 2015). In the United States, as in other high-income countries, birth defects are the main cause of infant mortality, being responsible for 1 out of 5 infant deaths (Petrini et al , 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Within the main causes of infant deaths in the United States, congenital malformations, deformations and chromosomal abnormalities appear in first place, representing 20.3% of total infant deaths in 2013 (Xu et al , 2016). These are also the reasons for 12% of all pediatric hospitalizations (Egbe et al , 2015). In Latin America, congenital anomalies are between the second and fifth cause of death in children under 1 year of age (Bronberg et al.…”
Section: Introductionmentioning
confidence: 99%
“…Congenital anomalies (CAs) are the leading cause of death and morbidity in children. 1 An appropriate detection and prompt treatment are essential to reduce complications in these children. Multiple approaches have been made to better identify and study CAs.…”
Section: Introductionmentioning
confidence: 99%